An efficient method for selecting and scaling ground motions matching target response spectrum mean and variance. (13th January 2016) - Ha, Seong Jin; Han, Sang Whan
Summary: The purpose of this study is to propose an accurate and efficient method for selecting and scaling ground motions matching target response spectrum mean and variance, which does not require excessive computation and simulation. In the proposed method, a desired number of ground motions are sequentially scaled and selected from a ground motion library without iterations. Copyright © 2016 John Wiley & Sons, Ltd.